2021
DOI: 10.3390/polym13111688
|View full text |Cite
|
Sign up to set email alerts
|

High-Strength GO/PA66 Nanocomposite Fibers via In Situ Precipitation and Polymerization

Abstract: The uniform dispersion of graphene oxide (GO) and strong interfacial bonding are the key factors in achieving the high mechanical strength of GO/polymer composites. It is still challenging to prepare GO/PA66 composites with uniform GO dispersion by the in situ polymerization method. In this paper, we prepare GO/PA66 salt nanocomposite by in situ precipitating PA66 salt with GO in ethanol. The GO/PA66 nanocomposite fibers are then fabricated using the as-prepared GO/PA66 salt by in situ polymerizing and melt sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…For the GA film, the broad stretching band at 3000 to 3750 cm −1 (amide A) was related to N-H stretching vibrations and O-H, and three characteristic peaks of GA were observed at around 1647 cm −1 (amide I) corresponding to C=O and C-N stretching vibrations, 1542 cm −1 (amide II) corresponding to N-H bending and C-H stretching vibration, and 1259 cm −1 (amide III) [9,36]. For PA66 film, the adsorption peak appearing at 3305 cm −1 belonged to the N-H stretching band of amine group and the peaks at 1641 cm −1 and 1540 cm −1 [37]; and the characteristic peak at 2934 cm −1 corresponding to the stretching vibration of C-H also confirmed solid evidence of the existence of PA66 [38]. The absence of peak splitting in all mixed nanofibers indicates that gelatin and PA66 were uniformly dispersed in the fibers.…”
Section: Ftir Spectra Analysismentioning
confidence: 55%
See 1 more Smart Citation
“…For the GA film, the broad stretching band at 3000 to 3750 cm −1 (amide A) was related to N-H stretching vibrations and O-H, and three characteristic peaks of GA were observed at around 1647 cm −1 (amide I) corresponding to C=O and C-N stretching vibrations, 1542 cm −1 (amide II) corresponding to N-H bending and C-H stretching vibration, and 1259 cm −1 (amide III) [9,36]. For PA66 film, the adsorption peak appearing at 3305 cm −1 belonged to the N-H stretching band of amine group and the peaks at 1641 cm −1 and 1540 cm −1 [37]; and the characteristic peak at 2934 cm −1 corresponding to the stretching vibration of C-H also confirmed solid evidence of the existence of PA66 [38]. The absence of peak splitting in all mixed nanofibers indicates that gelatin and PA66 were uniformly dispersed in the fibers.…”
Section: Ftir Spectra Analysismentioning
confidence: 55%
“…Figure 2b shows the XRD results of the GA, PA66 films and GA/PA66 films with various weight ratios. PA66 has two obvious diffraction peaks at around 2θ = 20.1° ascribed to the interchain hydrogen bond plane of the amide group [29] and 2θ = 23.7°, which is similar to the results of Noguchi's study [39]; whereas gelatin had a broad diffraction peak at 2θ = 19.2°, suggesting a low crystallinity of GA. For the GA/PA66 composite films, two diffraction peaks appeared between 20° and 25°, which were corresponding to the two characteristic peaks (α1 and α2) of the α-crystalline form of PA66 [38]. It was noticeable that the intensity of the peaks of the GA/PA66 composite film was enhanced compared to the pure GA film, suggesting that the crystallization of the GA/PA66 composite films was advanced with the addition of PA66.…”
Section: Xrd Analysismentioning
confidence: 97%
“…Studies have shown that increasing the alkyl chain length of the surface improves the interactions between the particles and the polymer matrix [ 27 ]. Therefore, several works proposed modifying inorganic filler particles with long-chain polymers [ 28 , 29 , 30 ]. Grafting such polymers on the particle surfaces has several advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GO and rGO can give more stable dispersions in water and polar solvents than graphene. In particular, Gu et al reported the modification of GO with polyamide in ethanol followed by melt spinning [ 35 ]. The developed composites provided excellent mechanical properties.…”
Section: Introductionmentioning
confidence: 99%